Effect of individualized end-inspiratory pause guided by driving pressure on respiratory mechanics during prone spinal surgery: a randomized controlled trial - Zhang, Ting; Lv, Feng; He, Shuangyu; Zhang, Yuntian; Ren, Li; Jin, Juying (Frontiers in Medicine, 2025)
PurposeThe prone position is commonly used in spinal surgery, but it can lead to decreased lung compliance and increased airway pressure. This study aimed to evaluate the effect of individualized end-inspiratory pause guided by driving pressure on respiratory mechanics in patients undergoing prone spinal surgery.MethodsA randomized controlled trial was conducted from August to October 2023. Patients scheduled for elective prone spinal surgery were randomly assigned to either a study group, receiving individualized end-inspiratory pause, or a control group, receiving a fixed end-inspiratory pause (10% of total inspiratory time). Mechanical ventilation parameters, including tidal volume, plateau pressure, driving pressure, and peak pressure, were recorded at different time points. Arterial blood gases were collected at baseline and at specified intervals.ResultsData from 36 subjects (18 in each group) were included in the final analysis. The study group exhibited a significant increase in respiratory system compliance (P < 0.05) and improved intraoperative oxygenation (P < 0.05). In addition, the individualized end-inspiratory pause significantly decreased plateau pressure (P < 0.05) and driving pressure (P < 0.05) compared to the control group.ConclusionThe individualized end-inspiratory pause guided by driving pressure effectively optimized pulmonary compliance and improved oxygenation during prone spinal surgery. These findings suggest that this ventilation strategy may enhance respiratory mechanics and reduce the risk of postoperative pulmonary complications.